The Positive Allosteric Modulation of alpha7-Nicotinic Cholinergic Receptors by GAT107 Increases Bacterial Lung Clearance in Hyperoxic Mice by Decreasing Oxidative Stress in Macrophages - Alex G. Gauthier; Jiaqi Wu; Mosi Lin; Ravikumar Sitapara; Abhijit Kulkarni; Ganesh A. Thakur; Edward E. Schmidt; Jeanette C. Perron; Charles R. Ashby; Lin L. Mantell (MDPI AG, 2021)
Supplemental oxygen therapy with supraphysiological concentrations of oxygen (hyperoxia; >21% O2) is a life-saving intervention for patients experiencing respiratory distress. However, prolonged exposure to hyperoxia can compromise bacterial clearance processes, due to oxidative stress-mediated impairment of macrophages, contributing to the increased susceptibility to pulmonary infections. This study reports that the activation of the α7 nicotinic acetylcholine receptor (α7nAChR) with the delete allosteric agonistic-positive allosteric modulator, GAT107, decreases the bacterial burden in mouse lungs by improving hyperoxia-induced lung redox imbalance. The incubation of RAW 264.7 cells with GAT107 (3.3 µM) rescues hyperoxia-compromised phagocytic functions in cultured macrophages, RAW 264.7 cells, and primary bone marrow-derived macrophages. Similarly, GAT107 (3.3 µM) also attenuated oxidative stress in hyperoxia-exposed macrophages, which prevents oxidation and hyper-polymerization of phagosome filamentous actin (F-actin) from oxidation. Furthermore, GAT107 (3.3 µM) increases the (1) activity of superoxide dismutase 1; (2) activation of Nrf2 and (3) the expression of heme oxygenase-1 (HO-1) in macrophages exposed to hyperoxia. Overall, these data suggest that the novel α7nAChR compound, GAT107, could be used to improve host defense functions in patients, such as those with COVID-19, who are exposed to prolonged periods of hyperoxia.